Epistemological Questions of Modern Physics - Kvasz, Ladislav (Organon F, 2005)
The aim of the paper is to describe the main epistemological ruptures in the history of modern physics. Our approach is based on the reconstruction of the formal language of physical theories. We examine how particular aspects of the formal language, such as its analytical, expressive, or explanatory power, as well as its analytical and expressive boundaries, have changed in the course of the historical development of physics. In the closing part of the paper we discuss the results of our historical reconstruction from several viewpoints.